THE NOUN PHRASE AND ITS QUALITY OF CATEGORY SHIFT USED IN THE NOVEL THE FAULT IN OUR STARS BY JOHN GREEN - Choirunnisa Choirunnisa; Ardayati Ardayati; Ani Fiani (English Journal Literacy Utama, 2023)
This research aimed to find out what types of category shifts were used in noun phrases and to find out quality assessments in the novel The Fault in Our Stars by John Green. The researcher used a descriptive qualitative method to analyze the noun phrases of category shift used in the novel. Data collection techniques used reading the novels, identifying the noun phrase found in both novels, finding the meaning of the words and phrases, and classifying them. Data analysis techniques used data reduction, data display, and drawing conclusions. The results showed that 102 data of category shifts were found in this research. There were 47 data for structure shift as the highest frequency and 6 data for class shift as the lowest frequency. Unit shifts found in this research were 38 data, and intra-system shifts occurred with 11 data. In the quality assessment of the category shift aspects, there were 78 data (76,5%) categorized as accurate. 20 data (19,65%) were less accurate, and 4 data (3,9%) were inaccurate. Moreover, in the acceptable aspect, the researcher found 92 data (90,2%) were acceptable, 9 data (8,8%) were less acceptable, and 1 data (0,98%) was unacceptable. The last aspect was readable; 90 data (88,2%) were readable, 9 data (8,8%) were less readable, and 3 data (2,9% ) were not readable. The conclusion of this research was the highest frequency of category shift was structure shift, and the lowest frequency was class shift. For quality assessment, the acceptable translation gained the biggest frequency, while the unacceptable got the lowest frequency in this research.